On Planning of Investments into City Development - Vladimir Nikolaevich Naumov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article deals with questions of planning the allocation of scarce resources in the development of St. Petersburg based on solving the optimization problem